Efektivitas Penggunaan Sistem Informasi Rencana Umum Pengadaan (SIRUP) di Dinas Pertanian Kabupaten Asahan - Piandayani, Pipin; Ginting, Simson (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This study aims to describe and examine effectiveness The Procurement General Plan Information System (SIRUP) in Department of Agriculture Asahan. This research uses a descriptive method with a qualitative approach. Data collection was carried out using structured observation, documentation, literature study, and in-depth interviews through purposive and snowball sampling. The results of this study indicate that the effectiveness of the use of the General Procurement Planning Information System (SIRUP) at the Asahan District Agriculture Office has been going quite well but cannot be said to be effective, because there are still obstacles encountered in its use. This can be seen from the SIRUP Admin who inputs data outside working hours so that he can enter data into the General Procurement Planning Information System (SIRUP), and the input is not carried out all at once which causes the use of the General Procurement Plan Information System (SIRUP) to not run effectively. But in terms of announcing the General Procurement Plan (RUP) it is quite easy for the Asahan District Agriculture Service.